2021
DOI: 10.3389/fpos.2021.685199
|View full text |Cite
|
Sign up to set email alerts
|

Economic Crisis and Attitudes Towards Democracy: How Ideology Moderates Reactions to Economic Downturns

Abstract: This paper studies the extent to which economic crises bust different reactions depending on individual ideological identity. Our argument is that individual left-right identification shapes how citizens evaluate the functioning of democracy, and consequently, it moderates the impact of economic crises on democratic discontent. We argue that left-wing individuals’ views on democratic performance would be more heavily affected by economic results and strongly shaped by the (in)capacity of a democracy to represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…We here focus on left-right ideology since it has a straightforward connection to perceptions of inequality, and previous studies have shown that the impact of central political attitudes may differ substantially depending on ideology (Christensen and von Schoultz, 2019). Previous studies have also shown that ideology may moderate how inequality affects political behaviour (Armingeon and Weisstanner, 2021;Jurado and Navarrete, 2021). The left-right ideological dimension is usually seen as the ideological dimension structuring most political conflicts (Downs, 1957), which in Europe has divided politics into the liberal-conservative right and the social-democratic or socialist left.…”
Section: Sociotropic Perceptions Of Inequality Have Different Links T...mentioning
confidence: 99%
“…We here focus on left-right ideology since it has a straightforward connection to perceptions of inequality, and previous studies have shown that the impact of central political attitudes may differ substantially depending on ideology (Christensen and von Schoultz, 2019). Previous studies have also shown that ideology may moderate how inequality affects political behaviour (Armingeon and Weisstanner, 2021;Jurado and Navarrete, 2021). The left-right ideological dimension is usually seen as the ideological dimension structuring most political conflicts (Downs, 1957), which in Europe has divided politics into the liberal-conservative right and the social-democratic or socialist left.…”
Section: Sociotropic Perceptions Of Inequality Have Different Links T...mentioning
confidence: 99%
“…Although the literature questioning the link between ideological preferences and political participation of all kinds is well developed, while the one connecting ideology and vote choice is abundant, the impact on democratic preferences remains much less substantial (Ceka and Magalhães 2016;Jurado and Navarrete 2021). That is the reason why, inspired by the above-mentioned argument of an affinity between citizens' participation and left-wing values, some scholars have brought in the idea that the support for the enlargement of participatory opportunities and the use of policy instruments that would give a greater role to citizens in decision-making might be driven by where people stand on the left/right cleavage.…”
Section: Support For Referendums Among Votersmentioning
confidence: 99%
“…People with varying ideological backgrounds have differing experiences during an economic crisis. Using survey data from 2002 to 2014 in Spain, Jurado and Navarrete (2021) concluded that the impact of economic crises greatly depends on the citizen's ideological identity.…”
Section: Economic Crises and Political Behavior And Attitudesmentioning
confidence: 99%